Reality bites: highlighting the potential discrepancies between multisensory taste perception in extended and physical reality - Dawes, Christopher; Beganovic, Sabina; Schwalk, Matti; Mai, Michaela; Pawlizak, Steve; Zhang, Jingxin; Nelles, Gabriele; Krasteva, Nadejda; Obrist, Marianna (Frontiers in Computer Science, 2023)
When we taste, we take in a variety of sensory information that can be completely independent from the properties of the food itself: the ambient lighting and environmental sounds can all influence our taste perception and affective responses. However, current multisensory research is mixed as to whether these In Real Life (IRL) findings also apply to Extended Reality (XR) environments. A potential reason for this may be the limited realism of some XR scenarios, which this study aimed to overcome through an immersive Virtual Reality experience (VR, chosen for its greater realism relative to other XR applications) whilst also expanding the scope to flavour perception. A total of 34 participants rated food samples under neutral, red, and green ambient lighting in VR. Participants ate either lime flavoured, strawberry flavoured, or ‘Neutral’ (no added flavour) samples. While participants were equally immersed in all three environments, they rated the red and green lighting environments as substantially less natural than the neutral lighting environment. Interestingly, while participants associated sweetness and sourness with red lighting and green lighting respectively, this minimally extended to their behavioural ratings, when sampling the stimuli in VR. Samples eaten under red lighting were rated as significantly sweeter than those eaten under neutral lighting. However, neither red nor green lighting affected sample sourness nor the intensity of strawberry or lime flavour. This study found limited evidence of multisensory integration in XR, wherein taste expectations do not extend to taste experiences. We discuss these results in light of prior works on crossmodal associations and raise a reflection on why multisensory integration of taste may not apply to XR in our study. While there is much excitement about the opportunities XR can offer, we argue that we are only at the beginning of understanding the experiences on the reality-virtuality continuum and that we need to establish a richer understanding of participants’ experiences, expectations, and taste/flavour perceptions between IRL and XR.